Kajian Karakteristik Fisikokimia dan Organoleptik Tepung Salak Sidimpuan (Salacca sumatrana) - Ifmalinda Ifmalinda; Andasuryani Andasuryani; Husein Lubis (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2019)
Zalacca Sidimpuan (Salacca sumatrana) is one of the salak fruit found in Indonesia. The characteristics of this type of zalacca have a distinctive shape, aroma and taste. During the harvest and overproduction, one of the efforts that can be done is to diversify food processing, namely retention. The handling in the process of shading will have an impact on the physicochemical properties of the resulting flour One of them is by giving immersion treatment and slice thickness variation. The purpose of this study was to examine the physicochemical characteristics of zalacca flour. The process of this research includes stripping the skin, separating fruit flesh with seeds, slicing with thickness (2 mm, 4 mm and 6 mm) and soaking with sodium metabisulfite concentration of 1.5 gr for 10 minutes, soaking with water and control (without soaking). The results showed that zalacca had a moisture content of 78%. Zalacca flour which has the highest water content of 11.945% in the control treatment (without immersion) 6 mm slice thickness. Salak flour which has the highest vitamin C level of 0.0585% in the control treatment (without soaking) the slice thickness is 2 mm. Zalacca flour has the highest percentage of fineness of flour 27,745% in the control treatment (without soaking) slice thickness of 2 mm. Zalacca flour which has the highest bulk density of 0.701 gr / ml on the soaking treatment of sodium metabisulfite slices thickness of 4 mm. Zalacca flour which has the highest hue of 57.9 ° on the treatment of soaking sodium metabisulfite slices thickness of 2 mm.